Hollow fiber membrane as well as preparation method and application thereof
By solidly loading cationic copolymers on the inner surface of the hollow fiber membrane, the endotoxins in the dialysate are specifically adsorbed, and the problem of insufficient interception ability of the hollow fiber membrane in the prior art is solved, thereby achieving higher dialysate purity and lower infection risk.
Patent Information
- Application Number
- CN202411736665.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, the hollow fiber membrane has limited ability to intercept and adsorb endotoxins, which affects the purity of the dialysate and increases the risk of infection in patients.
By solidly loading cationic copolymers on the inner surface of the hollow fiber membrane, the endotoxin in the dialysate is specifically adsorbed on the inner layer of the hollow fiber membrane by using electrostatic force, thereby improving the purity of the dialysate.
Effectively intercept the endotoxins in the dialysate, improve the purification degree of the dialysate, reduce the risk of infection in patients, and improve the hydrophilicity and hemocompatibility of the hollow fiber membrane, improve the treatment efficiency of the dialysate.
Smart Images

Figure CN119549001A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of blood purification materials, and in particular to a hollow fiber membrane and a preparation method and application thereof. Background Art
[0002] The dialysate in the hemodialysis circulation needs to be filtered by the dialysate filter before being introduced into the dialyzer for use. The dialysate filter is a Class III medical device and is generally replaced after 3 to 6 months of clinical use. The filtering performance of the dialysate filter will drop significantly after the later use. If the dialysate filter cannot filter out the endotoxins and microorganisms carried in the dialysate, the unclean dialysate will be introduced into the dialysate filter, which will increase the risk of infection for the patient.
[0003] The working principle of the dialysate filter currently on the market is to use the principle of semi-permeable membrane to filter out harmful substances such as impurities, bacteria and endotoxins in the dialysate through the micropores of the hollow fiber membrane, thereby improving the purity of the dialysate. However, the hollow fiber membrane in the prior art has limited interception and adsorption capacity for endotoxins, which affects the purity of the dialysate. Summary of the invention
[0004] The present invention aims to solve the above-mentioned defects of the prior art and provide a hollow fiber membrane capable of specifically adsorbing endotoxins. The hollow fiber membrane has good interception and adsorption capabilities for endotoxins and impurities, which is beneficial to improving the purity of the dialysate.
[0005] In order to solve the above problems, the present invention provides a method for preparing a hollow fiber membrane, comprising the following steps:
[0006] The first polymer, the pore-forming agent, the cationic copolymer and the first solvent are uniformly mixed to obtain a first spinning solution, wherein the cationic copolymer is a hydrophilic cationic copolymer;
[0007] uniformly mixing the second polymer, the pore-forming agent and the first solvent to obtain a second spinning solution;
[0008] The core liquid, the first spinning solution and the second spinning solution are distributed from the inside to the outside in sequence and extruded simultaneously to form an initial membrane. After the initial membrane is solidified, a hollow fiber membrane is obtained, and the inner surface layer of the hollow fiber membrane is fixed with the cationic copolymer.
[0009] The second aspect of the present invention provides a hollow fiber membrane, which is prepared by the preparation method as described in the first aspect, and the inner surface layer of the hollow fiber membrane is immobilized with a cationic copolymer.
[0010] The third aspect of the present invention provides a hollow fiber membrane prepared by the preparation method as described in the first aspect, or use of the hollow fiber membrane as described in the second aspect in hemodialysis.
[0011] The preparation method of the hollow fiber membrane described in the present invention comprises the following steps: adding a cationic copolymer to a first spinning solution, and arranging the first spinning solution between a core solution and a second spinning solution; after solidification into a membrane, the first spinning solution solidifies to form an inner layer of the hollow fiber membrane, and the second spinning solution solidifies to form an outer layer of the hollow fiber membrane; the cationic copolymer is immobilized in the inner layer; when the dialysate enters the hollow fiber membrane from the hollow channel of the hollow fiber membrane, the cationic copolymer in the inner layer directly contacts the dialysate; the cationic copolymer with cations combines with endotoxins in the dialysate through electrostatic force, so that the endotoxins in the dialysate are specifically adsorbed in the inner layer of the hollow fiber membrane, and will not pass through the hollow fiber membrane into the outer layer. The filter side can effectively intercept the endotoxin in the dialysate and improve the degree of purification of the dialysate; by separately regulating the film-making formula of the first spinning solution and the second spinning solution, the outer layer of the hollow fiber membrane can be solidified to form a sponge-like structure with a pore size gradually increasing from the inside to the outside, improve the screening ability of the hollow fiber membrane, and improve the processing efficiency of the dialysate, and the inner layer of the hollow fiber membrane can specifically adsorb endotoxins, and the inner layer and the outer layer are combined to make the hollow fiber membrane not only specifically adsorb endotoxins, but also improve the ability of the hollow fiber membrane to remove other impurities, and the first spinning solution and the second spinning solution can improve the hydrophilicity of the hollow fiber membrane, which is conducive to improving the blood compatibility of the hollow fiber membrane. In the present invention, by extruding the core liquid, the first spinning solution and the second spinning solution simultaneously to form an initial membrane, the initial membrane can be formed in one step, which is conducive to realizing the mass production of the hollow fiber membrane, and is conducive to reducing the production cost of the hollow fiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 A flow chart of preparing a hollow fiber membrane provided by an embodiment of the present invention;
[0013] Figure 2 A schematic structural diagram of a three-hole annular spinneret provided in an embodiment of the present invention;
[0014] Figure 3 This is a SEM image of a hollow fiber membrane prepared in one embodiment of the present invention. DETAILED DESCRIPTION
[0015] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0016] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0017] In addition, the terms "comprising", "including", "containing", and "having" are not restrictive, that is, other steps and other components that do not affect the results can be added. Unless otherwise specified, materials, equipment, and reagents are commercially available.
[0018] In addition, although the present invention describes the steps in the preparation in the form of S110, S120, S130, etc., this description is only for ease of understanding, and the form of S110, S120, S130, etc. does not limit the sequence of the steps.
[0019] Figure 1 A flow chart of preparing a hollow fiber membrane according to an embodiment of the present invention. Figure 1 As shown, the first aspect of the embodiment of the present application provides a method for preparing a hollow fiber membrane, comprising the following steps:
[0020] Step S110, uniformly mixing a first polymer, a pore-forming agent, a cationic copolymer and a first solvent to obtain a first spinning solution, wherein the cationic copolymer is a hydrophilic cationic copolymer.
[0021] Specifically, in parts by weight, 15 to 30 parts of the first polymer, 1 to 10 parts of the pore-forming agent, 1 to 10 parts of the cationic copolymer and 38 to 95 parts of the first solvent are mixed, and stirred at 30°C to 90°C for 12h to 24h, and after vacuum degassing and static degassing, a first spinning solution is prepared. Exemplarily, if the total weight is 100 parts, 15wt% to 30wt% of the first polymer, 1wt% to 10wt% of the pore-forming agent, 1wt% to 10wt% of the cationic copolymer and 38wt% to 95wt% of the first solvent are mixed. Thus, a cationic copolymer is added to the first spinning solution, and the cationic copolymer with cations can be combined with negatively charged endotoxins through electrostatic forces, so that the cationic copolymer can selectively adsorb endotoxins and avoid adsorbing nonspecific proteins to effectively remove endotoxins. By limiting the usage ratio of each component in the first spinning solution within the above-mentioned range, the solid loading capacity of the cationic copolymer can be increased, the clearance rate of endotoxin can be improved, and the pore size of the inner layer of the hollow fiber membrane can be adjusted to an appropriate range, which is beneficial to reduce the filtration resistance of the hollow fiber membrane and improve the efficiency of blood purification.
[0022] Wherein, the cationic copolymer is a combination of one or more of polyvinyl amide, diethylenediamine, polylysine, and vinyl pyrrolidone-dimethylaminoethyl methacrylate copolymer. Thus, the above-mentioned several substances as cationic copolymers not only have good hydrophilicity, but also can improve the hydrophilicity of the inner surface of the hollow fiber membrane, and the above-mentioned several substances can be dissolved in the first solvent, which is conducive to improving the uniformity and stability of the first spinning solution mixing, avoiding the first spinning solution from stratifying, and affecting the filtration performance of the inner layer of the hollow fiber membrane. Preferably, the cationic copolymer is vinyl pyrrolidone-dimethylaminoethyl methacrylate (i.e., PVP-Q), which is a derivative of polyvinyl pyrrolidone, similar to the structure of polyvinyl pyrrolidone, and it also has a certain pore-forming effect and good hydrophilicity.
[0023] The first polymer is a combination of one or more of polysulfone, polyethersulfone, polypropylene and polyvinylidene fluoride. Therefore, the above substances have excellent biocompatibility, and using these substances as the first polymer is conducive to improving the biocompatibility of the inner layer of the hollow fiber membrane.
[0024] The pore-forming agent is a combination of one or more of polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, and polyvinyl alcohol. Therefore, the above substances can not only form pores and improve the adsorption of the hollow fiber membrane, but also have good hydrophilicity and can improve the hydrophilicity of the inner layer of the hollow fiber membrane.
[0025] The first solvent is at least two of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and purified water, and the mass percentages of at least two first solvents are different. On the basis of the above embodiment, as an optional implementation, the weight of one first solvent is 3 to 15 parts, and the weight of another first solvent is 35 to 80 parts. Therefore, selecting the above substances as the first solvent and selecting two different first solvents to form a composite first solvent is beneficial to improve the uniformity and stability of the mixing of the first spinning solution, so that after the hollow fiber membrane is obtained, the various components of the inner layer of the hollow fiber membrane can be more closely connected together.
[0026] On the basis of the above embodiment, as a preferred embodiment, 16 parts of the first polymer, 2 parts of the pore-forming agent, 2 to 3 parts of the cationic copolymer and 79 to 80 parts of the first solvent are mixed by weight to prepare a first spinning solution. Thus, the dosage ratio of each component in the first spinning solution is limited within the above range, on the one hand, it can avoid excessive content of the pore-forming agent and the cationic copolymer, so that the pore size of the inner layer of the hollow fiber membrane is too large, and the spinning is poor, so that endotoxin passes through the pores of the side wall of the hollow fiber membrane to the filtrate, on the other hand, it can also avoid the content of the cationic copolymer is too low, affecting the clearance rate of endotoxin, so the pore-forming agent and the cationic copolymer in the first spinning solution are within the above range, which can balance the pore size of the inner layer of the hollow fiber membrane and the clearance rate of endotoxin, not only can the hollow fiber membrane maintain a good molecular weight cutoff and filtration rate, but also greatly increase the endotoxin clearance rate, and greatly reduce the inner wall contact angle, improve the hydrophilicity of the inner layer of the hollow fiber membrane, which is conducive to greatly improving the purity of the dialysate, and is conducive to improving the service life of the dialysate filter.
[0027] Step S120: uniformly mix the second polymer, the pore-forming agent and the first solvent to obtain a second spinning solution.
[0028] Specifically, in parts by weight, 15 to 30 parts of the second polymer, 1 to 15 parts of the pore-forming agent, and 43 to 96 parts of the first solvent are mixed, and stirred at 30°C to 90°C for 12h to 24h, and after vacuum degassing and static degassing, a second spinning solution is obtained. Exemplarily, if the total weight is 100 parts, a second polymer with a mass percentage of 15wt% to 30wt%, a pore-forming agent of 1wt% to 15wt%, and a first solvent of 43wt% to 96wt% are mixed. Thus, by limiting the amount ratio of each component in the second spinning solution to the above range, the outer layer of the hollow fiber membrane with a sponge-like structure can be obtained, which is beneficial to improve the screening effect of the hollow fiber membrane, thereby improving the ability of the hollow fiber membrane to remove impurities.
[0029] Wherein, the second polymer is a combination of one or more of polysulfone, polyethersulfone, polypropylene, polyvinylidene fluoride and sulfonated polyethersulfone. Therefore, the above-mentioned substances have excellent biocompatibility, and using these substances as the second polymer is conducive to improving the biocompatibility of the outer layer of the hollow fiber membrane, and the structure of the second polymer is similar to that of the first polymer. In the process of membrane formation, the interface molecules of the inner layer of the hollow fiber membrane and the outer layer of the hollow fiber membrane can be more firmly entangled, thereby improving the strength of the combination of the two, which is conducive to improving the structural stability of the hollow fiber membrane.
[0030] The pore-forming agent is a combination of one or more of polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, and polyvinyl alcohol. Therefore, the above substances can not only form pores and improve the adsorption of the hollow fiber membrane, but also have good hydrophilicity and can improve the hydrophilicity of the outer layer of the hollow fiber membrane.
[0031] The first solvent is at least two of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and purified water, and the mass percentages of the two first solvents are different. On the basis of the above embodiment, as an optional implementation, the weight of one first solvent is 3 to 15 parts, and the weight of the other first solvent is 40 to 81 parts. Therefore, selecting the above substances as the first solvent and selecting two different first solvents to form a composite first solvent is beneficial to improve the uniformity and stability of the mixing of the second spinning solution, so that after the hollow fiber membrane is obtained, the various components of the outer layer of the hollow fiber membrane can be more closely connected together.
[0032] In step S130, the core liquid, the first spinning solution and the second spinning solution are sequentially distributed from the inside to the outside and extruded simultaneously to form an initial membrane. After the initial membrane is solidified, a hollow fiber membrane is obtained, and the inner surface layer of the hollow fiber membrane is immobilized with a cationic copolymer.
[0033] Specifically, the core liquid, the first spinning solution and the second spinning solution are filtered through filters of different sizes, and then transported to a three-hole annular spinneret through a pump and extruded simultaneously to obtain an initial membrane, wherein the three-hole annular spinneret includes a core liquid channel, a first spinning solution channel and a second spinning solution channel arranged sequentially from the inside to the outside, the core liquid is extruded from the core liquid channel, the first spinning solution is extruded from the first spinning solution channel, and the second spinning solution is extruded from the second spinning solution channel, so that the core liquid, the first spinning solution and the second spinning solution are distributed sequentially from the inside to the outside. After the initial membrane is obtained, the initial membrane is sequentially solidified and collected through an air section, a gel section, a water washing section and a drying section to obtain a hollow fiber membrane. Thus, the first spinning solution is arranged between the core solution and the second spinning solution. After the hollow fiber membrane is obtained, the first spinning solution solidifies to form the inner layer of the hollow fiber membrane, and the second spinning solution solidifies to form the outer layer of the hollow fiber membrane, and the cationic copolymer is immobilized in the inner layer. The dialysate enters the hollow fiber membrane from the hollow channel inside the hollow fiber membrane. The cationic copolymer in the inner layer directly contacts the dialysate and adsorbs endotoxin in the dialysate, which is beneficial to better purify the dialysate, and is beneficial to increase the purification flow rate of the dialysate and improve the treatment efficiency of the dialysate; the initial membrane passes through the air section, gel section, water washing section and drying section in sequence, which can gradually increase the pore size of the hollow fiber membrane from the inside to the outside, and the inner layer of the hollow fiber membrane is denser. The hollow fiber membrane with this structure can reduce the resistance in the process of dialysate purification, which is beneficial to improve the efficiency of dialysate purification.
[0034] Figure 2 Schematic diagram of the structure of a three-hole annular spinneret. Figure 2 As shown, the three-hole annular spinneret includes a core liquid channel 200, a first spinning solution channel 210 and a second spinning solution channel 220 which are arranged in sequence from the inside to the outside. The core liquid channel 200 is a circular channel, the first spinning solution channel 210 and the second spinning solution channel 220 are annular channels, and the core liquid channel 200, the first spinning solution channel 210 and the second spinning solution channel 220 are arranged in sequence from the inside to the outside.
[0035] Based on the above embodiment, as an optional implementation manner, the relative humidity of the air section is 30% to 99%, the temperature of the gel section is 30°C to 80°C, the temperature of the washing section is 70°C to 95°C, the temperature of the drying section is 100°C to 140°C, and the spinning speed is 15m / min to 25m / min. Therefore, the relative humidity of the air section is set within the above range, and the water content in the core liquid is relatively high. After the core liquid, the first spinning solution and the second spinning solution are extruded from the three-hole annular spinneret, the water in the core liquid contacts the first spinning solution and the second spinning solution through the air section with high relative humidity, which can promote the solidification of the hollow fiber membrane and cause a drastic phase transition, so that the viscous flow state is converted into a solid state to form a dense inner layer. At the same time, the second spinning solution will also undergo a phase transition to form an outer layer, which is beneficial to the further solidification of the inner and outer layers through the gel section, and is beneficial to the entanglement and connection between the interface molecules of the inner and outer layers, thereby improving the bonding strength and stability of the hollow fiber membrane; the residual solvents and other chemical substances in the hollow fiber membrane can be removed by washing with water to prevent the residual chemical substances from affecting the blood compatibility of the hollow fiber membrane; the moisture in the hollow fiber membrane can be removed by drying, which can eliminate internal stress and improve the dimensional stability of the hollow fiber membrane.
[0036] In this embodiment, the core liquid can be prepared by mixing purified water and an organic solvent. As an optional embodiment, the mass percentage of the organic solvent in the core liquid is 20% to 60%, preferably, the mass percentage of the organic solvent in the core liquid is 40% to 55%.
[0037] Based on the above embodiment, as an optional implementation, the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide. Therefore, when the core liquid forms the hollow structure of the hollow fiber membrane, the use of the above organic solvent is beneficial to improving the hydrophilicity and biocompatibility of the hollow fiber membrane, and the type of the organic solvent is the same as that of the first solvent, which is beneficial to the mutual diffusion between the core liquid and the first spinning solution, and improves the structural stability of the hollow fiber membrane.
[0038] In this embodiment, the wall thickness of the inner layer and the outer layer of the hollow fiber membrane can be adjusted by adjusting the pump speed of the first spinning solution, the second spinning solution and the feed pump. Generally speaking, the faster the pump speed, the thicker the wall thickness.
[0039] The preparation method of the hollow fiber membrane provided in the embodiment of the present application includes adding a cationic copolymer to a first spinning solution, and setting the first spinning solution between a core solution and a second spinning solution. After solidification into a membrane, the first spinning solution solidifies to form an inner layer of the hollow fiber membrane, and the second spinning solution solidifies to form an outer layer of the hollow fiber membrane. The cationic copolymer is immobilized in the inner layer. When the dialysate enters the hollow fiber membrane from the hollow channel of the hollow fiber membrane, the cationic copolymer in the inner layer directly contacts the dialysate. The cationic copolymer with cations combines with endotoxins in the dialysate through electrostatic force, so that the endotoxins in the dialysate are specifically adsorbed in the inner layer of the hollow fiber membrane, and will not pass through the hollow fiber membrane into the membrane. Into the filtration side, it can effectively intercept endotoxins in the dialysate and improve the purity of the dialysate; by separately regulating the membrane-making formula of the first spinning solution and the second spinning solution, the outer layer of the hollow fiber membrane can be solidified to form a sponge-like structure with a pore size gradually increasing from the inside to the outside, thereby improving the screening ability of the hollow fiber membrane and the processing efficiency of the dialysate, and the inner layer of the hollow fiber membrane can specifically adsorb endotoxins. By combining the inner layer and the outer layer, the hollow fiber membrane can not only specifically adsorb endotoxins, but also improve the hollow fiber membrane's ability to remove other impurities, and the first spinning solution and the second spinning solution can improve the hydrophilicity of the hollow fiber membrane, which is beneficial to improving the blood compatibility of the hollow fiber membrane. In this embodiment, the core liquid, the first spinning solution and the second spinning solution are extruded simultaneously to form an initial membrane, so that the initial membrane can be formed in one step, which is beneficial to achieving mass production of the hollow fiber membrane and reducing the production cost of the hollow fiber membrane.
[0040] The second aspect of the embodiment of the present application provides a hollow fiber membrane, which is prepared by the preparation method described in the first aspect, and the inner surface of the hollow fiber membrane is immobilized with a cationic copolymer, the inner layer thickness of the hollow fiber membrane is 5μm to 15μm, and the outer layer thickness of the hollow fiber membrane is 25μm to 35μm. Thus, the inner layer thickness and outer layer thickness of the hollow fiber membrane are controlled within the above range, which is conducive to reducing the resistance of the hollow fiber membrane to dialyzing the dialysate, and is conducive to improving the efficiency of dialysate purification.
[0041] Figure 3 310 is the inner layer of the hollow fiber membrane, 320 is the outer layer of the hollow fiber membrane, and Figure 3 It can be seen that the inner layer is dense, thinner than the outer layer, the outer layer is loose, and the outer layer is a sponge-like structure with pore size gradually increasing from the inside to the outside.
[0042] The third aspect of the embodiment of the present application provides the application of the above-mentioned hollow fiber membrane in hemodialysis. During the hemodialysis process, the hollow fiber membrane can be used to filter the dialysate, which is beneficial to reduce the endotoxin content in the dialysate and improve the filtration efficiency of the dialysate and the service life of the dialysate filter.
[0043] In order to further explain the present invention in detail, the present invention will be further explained in conjunction with specific examples. The experimental methods used in the examples of the present invention are conventional methods unless otherwise specified; the materials, reagents, etc. used in the examples of the present invention are purchased from the market unless otherwise specified.
[0044] Example 1
[0045] This embodiment provides a method for preparing a hollow fiber membrane, comprising the following steps:
[0046] (1) 40 wt % of N,N-dimethylacetamide and 60 wt % of purified water were stirred at 80° C. to obtain a core liquid;
[0047] 16 wt % of polyethersulfone, 4 wt % of polyvinylpyrrolidone, 2 wt % of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 72 wt % of N,N-dimethylacetamide and 6 wt % of purified water were stirred and mixed at 80° C. for 24 h, and after vacuum degassing and static degassing, a first spinning solution was obtained;
[0048] 16 wt % of polyethersulfone, 4 wt % of polyvinylpyrrolidone, 74 wt % of N,N-dimethylacetamide and 6 wt % of purified water were stirred at 80° C. for 24 h, and after vacuum degassing and static degassing, a second spinning solution was prepared.
[0049] (2) The core liquid, the first spinning solution and the second spinning solution obtained in step (1) are filtered through filters of different sizes respectively, and then transported to a three-hole annular spinneret through a pump for simultaneous extrusion, so that the core liquid, the first spinning solution and the second spinning solution are distributed from the inside to the outside in sequence. After the initial membrane is obtained, the initial membrane is sequentially solidified and collected through an air section, a gel section, a water washing section and a drying section to obtain a hollow fiber membrane, wherein the relative humidity of the air section is 99%, the temperature of the gel section is 40°C, the temperature of the water washing section is 95°C, the temperature of the drying section is 120°C, and the spinning speed is 18 m / min.
[0050] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0051] Example 2
[0052] This embodiment provides a method for preparing a hollow fiber membrane. The method for preparing a hollow fiber membrane in this embodiment is the same as the method in Example 1, except that:
[0053] 16wt% of polyethersulfone, 2wt% of polyvinylpyrrolidone, 2wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 74wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred and mixed at 80°C for 24h, and the first spinning solution was obtained after vacuum degassing and static degassing.
[0054] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0055] Example 3
[0056] This embodiment provides a method for preparing a hollow fiber membrane. The method for preparing a hollow fiber membrane in this embodiment is the same as the method in Example 1, except that:
[0057] 16wt% of polyethersulfone, 1wt% of polyvinylpyrrolidone, 3wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 74wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred and mixed at 80°C for 24h, and the first spinning solution was obtained after vacuum degassing and static degassing.
[0058] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0059] Example 4
[0060] This embodiment provides a method for preparing a hollow fiber membrane. The method for preparing a hollow fiber membrane in this embodiment is the same as the method in Example 1, except that:
[0061] 16wt% of polyethersulfone, 2wt% of polyvinylpyrrolidone, 3wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 73wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred at 80°C for 24h, and after vacuum degassing and static degassing, a second spinning solution was obtained.
[0062] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0063] Example 5
[0064] This embodiment provides a method for preparing a hollow fiber membrane. The method for preparing a hollow fiber membrane in this embodiment is the same as the method in Example 1, except that:
[0065] 16wt% of polyethersulfone, 2wt% of polyvinylpyrrolidone, 2.2wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 73.8wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred at 80°C for 24h, and after vacuum degassing and static degassing, a second spinning solution was obtained.
[0066] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0067] Example 6
[0068] This embodiment provides a method for preparing a hollow fiber membrane. The method for preparing a hollow fiber membrane in this embodiment is the same as the method in Example 1, except that:
[0069] 16wt% of polyethersulfone, 2wt% of polyvinylpyrrolidone, 2.5wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 73.5wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred at 80°C for 24h, and after vacuum degassing and static degassing, a second spinning solution was obtained.
[0070] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0071] Example 7
[0072] This embodiment provides a method for preparing a hollow fiber membrane. The method for preparing a hollow fiber membrane in this embodiment is the same as the method in Example 1, except that:
[0073] 16wt% of polyethersulfone, 2wt% of polyvinylpyrrolidone, 2.7wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 73.3wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred at 80°C for 24h, and after vacuum degassing and static degassing, a second spinning solution was obtained.
[0074] The inner diameter of the hollow fiber membrane prepared in this embodiment is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0075] Comparative Example 1
[0076] This comparative example 1 provides a method for preparing a hollow fiber membrane. The method for preparing the hollow fiber membrane in this comparative example is the same as the method for preparing the hollow fiber membrane in Example 1, except that:
[0077] 16 wt % of polyethersulfone, 4 wt % of polyvinylpyrrolidone, 74 wt % of N,N-dimethylacetamide and 6 wt % of purified water were stirred and mixed at 80° C. for 24 hours, and a first spinning solution was obtained after vacuum degassing and static degassing.
[0078] The inner diameter of the hollow fiber membrane prepared in this comparative example is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0079] Comparative Example 2
[0080] This comparative example 2 provides a method for preparing a hollow fiber membrane. The method for preparing the hollow fiber membrane in this comparative example is the same as the method for preparing the hollow fiber membrane in Example 2, except that:
[0081] 16wt% of polyethersulfone, 2wt% of polyvinylpyrrolidone, 2wt% of vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, 74wt% of N,N-dimethylacetamide and 6wt% of purified water were stirred at 80°C for 24h, and after vacuum degassing and static degassing, a second spinning solution was obtained.
[0082] The inner diameter of the hollow fiber membrane prepared in this comparative example is 200 μm, and the wall thickness is 40 μm, wherein the inner layer thickness is 5 μm, and the outer layer thickness is 35 μm.
[0083] The hollow fiber membranes prepared in Examples 1 to 7 and Comparative Examples 1 to 2 are assembled into small components. The specific assembly method of the small components is not further limited in this embodiment. The technicians in this field can assemble according to the actual situation. The small components contain inlets, outlets and filtration ports. After being assembled into small components, the performance of each hollow fiber membrane is tested, mainly for endotoxin clearance, molecular weight cutoff and filtration rate. The specific test method is as follows:
[0084] 1. Endotoxin clearance test:
[0085] Endotoxin is quantitatively detected using a colorimetric method. The endotoxin content is detected by the amount of chromophore released by the specific substrate caused by the coagulase produced during the reaction of the horseshoe crab reagent with endotoxin, and the endotoxin level is calculated based on the colorimetry of the product.
[0086] A standard solution with an endotoxin concentration of 1Eu / mL was prepared, and a peristaltic pump was used to transport the solution to the inlet of the small component. The solution flowed out from the outlet and the filtration end to form a self-circulation. After adjusting the transmembrane pressure to 100 mmHg, the filtrate was collected from the filtration end for 5 minutes, and the endotoxin concentration on the filtration side was detected and divided by the initial concentration to obtain the endotoxin clearance rate data.
[0087] 2. Molecular weight cut-off detection:
[0088] A series of standard dextran with different molecular weights were selected and dissolved in water to prepare solutions of a certain concentration. The standard solutions were passed through a small component with a transmembrane pressure of 100 mmHg set and stabilized for 10 minutes. The filtrate was collected and the solute concentrations in the filtrate and the original solution were measured using GPC. A curve of retention rate versus molecular weight was drawn based on the filtration rates of multiple standard substances. The molecular weight corresponding to a retention rate of 90% was calculated, which was the molecular weight cutoff of the membrane.
[0089] 3. Filtration rate test:
[0090] Use a pump to send purified water to the hollow fiber membrane module, adjust the transmembrane pressure to a constant 100mmHg, and after membrane separation, use a measuring cylinder to collect the permeate, record the amount of water that permeates the membrane within a certain period of time, and the excess water flows back to the storage tank. Test three times, take the average value, and calculate the water flux.
[0091] The test results are shown in Table 1.
[0092] Table 1
[0093]
[0094] As can be seen from Table 1, compared with Example 1, no cationic copolymer was added to the first spinning solution of Comparative Example 1, and the endotoxin clearance rate of the hollow fiber membrane prepared in Comparative Example 1 was greatly reduced, and the inner wall contact angle was greatly improved, indicating that the hydrophilicity of the inner layer of the hollow fiber membrane in Comparative Example 1 is much lower than that of the hollow fiber membrane in Example 1, which also shows that adding a cationic copolymer in the first spinning solution can not only improve the ability of the hollow fiber membrane to remove endotoxins, but also improve the hydrophilicity of the inner layer of the hollow fiber membrane. Compared with Example 2, a cationic copolymer was added to the second spinning solution of Comparative Example 2, but the endotoxin clearance rate of the hollow fiber membrane prepared in Comparative Example 2 did not increase further, because the outer layer of the hollow fiber membrane is not directly in contact with endotoxins, adding a cationic copolymer to the outer layer of the hollow fiber membrane can not further improve the performance of the hollow fiber membrane, and the cationic copolymer in the inner layer of the hollow fiber membrane can fully remove endotoxins in the dialysate, and adding a cationic copolymer to the outer layer of the hollow fiber membrane will increase production costs and reduce production efficiency.
[0095] By comparing Example 1 and Example 2, it can be seen that when the content of the cationic copolymer is unchanged, increasing the content of the pore-forming agent will affect the pore size of the inner layer of the hollow fiber membrane, increase the pore size of the inner layer of the hollow fiber membrane, thereby significantly increasing the molecular weight cutoff and the filtration amount, which will also cause most of the endotoxins to pass through the pores of the hollow fiber membrane sidewalls to the filtrate, and the endotoxin clearance rate is greatly reduced. By comparing Example 2 and Example 3, it can be seen that when the cationic copolymer content is increased, although the endotoxin clearance rate can be significantly increased, the pore-forming agent content is reduced, which will reduce the pore size of the inner layer of the hollow fiber membrane, significantly reduce the molecular weight cutoff and the filtration amount, and greatly reduce the filtration efficiency.
[0096] As can be seen from Example 2 and Example 4 to 7, the content of each component in the first spinning solution is maintained within a suitable range, which is conducive to maintaining the balance between the pore-forming agent and the cationic copolymer, not only enabling the hollow fiber membrane to maintain a good molecular weight cut-off and filtration rate, but also greatly increasing the endotoxin clearance rate, and greatly reducing the inner wall contact angle, improving the hydrophilicity of the inner layer of the hollow fiber membrane, and being conducive to greatly improving the purity of the dialysate, and being conducive to improving the service life of the dialysate filter. In addition, as can be seen from Example 5 to Example 7, the content of the cationic copolymer is improved within a certain range, and the molecular weight cut-off and filtration rate of the prepared hollow fiber membrane are also increased therewith, and the endotoxin clearance rate and the inner wall contact angle are not significantly improved, because the vinyl pyrrolidone-dimethylamino ethyl methacrylate copolymer in the present embodiment is a derivative of the pore-forming agent polyvinyl pyrrolidone, which also has a certain pore-forming effect, and can also improve the hydrophilicity of the inner layer of the hollow fiber membrane. And the content of the cationic copolymer continues to increase the pore size of the inner layer of the hollow fiber membrane, thereby affecting the endotoxin clearance rate.
[0097] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a hollow fiber membrane, characterized in that: The steps include: The first polymer, the pore-forming agent, the cationic copolymer and the first solvent are uniformly mixed to obtain a first spinning solution, wherein the cationic copolymer is a hydrophilic cationic copolymer; uniformly mixing the second polymer, the pore-forming agent and the first solvent to obtain a second spinning solution; The core liquid, the first spinning solution and the second spinning solution are distributed from the inside to the outside in sequence and extruded simultaneously to form an initial membrane. After the initial membrane is solidified, a hollow fiber membrane is obtained, and the inner surface layer of the hollow fiber membrane is fixed with the cationic copolymer.
2. The preparation method according to claim 1, characterized in that: The cationic copolymer is a combination of one or more of polyvinyl amide, diethylenediamine, polylysine, and vinyl pyrrolidone-dimethylaminoethyl methacrylate copolymer.
3. The preparation method according to claim 1, characterized in that: The first polymer, the pore-forming agent, the cationic copolymer and the first solvent are uniformly mixed to prepare a first spinning solution, comprising: In parts by weight, 15 to 30 parts of a first polymer, 1 to 10 parts of a pore-forming agent, 1 to 10 parts of a cationic copolymer, and 38 to 95 parts of a first solvent are mixed, and stirred at 30° C. to 90° C. for 12 to 24 hours, and after vacuum degassing and static degassing, a first spinning solution is obtained; The first polymer is a combination of one or more of polysulfone, polyethersulfone, polypropylene and polyvinylidene fluoride.
4. The preparation method according to claim 3, characterized in that: The first spinning solution is prepared by mixing 16 parts of the first polymer, 2 parts of the pore-forming agent, 2 to 3 parts of the cationic copolymer and 79 to 80 parts of the first solvent in parts by weight.
5. The preparation method according to claim 1, characterized in that: The second polymer, the pore-forming agent and the first solvent are uniformly mixed to obtain a second spinning solution, comprising: In parts by weight, 15 to 30 parts of a second polymer, 1 to 15 parts of a pore-forming agent, and 43 to 96 parts of a first solvent are mixed, and stirred at 30° C. to 90° C. for 12 to 24 hours, and after vacuum degassing and static degassing, a second spinning solution is prepared; The second polymer is a combination of one or more of polysulfone, polyethersulfone, polypropylene, polyvinylidene fluoride and sulfonated polyethersulfone.
6. The preparation method according to claim 3 or 5, characterized in that: The pore-forming agent is a combination of one or more of polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, and polyvinyl alcohol; The first solvent is at least two of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and purified water, and the mass percentages of at least two of the first solvents are different.
7. The preparation method according to claim 1, characterized in that: The initial film is cured, comprising: The initial film is solidified by passing through an air section, a gel section, a water washing section and a drying section in sequence, wherein the relative humidity of the air section is 30% to 99%, the temperature of the gel section is 30° C. to 80° C., the temperature of the water washing section is 70° C. to 95° C., and the temperature of the drying section is 100° C. to 140° C.
8. A hollow fiber membrane, characterized in that: The hollow fiber membrane is prepared by the preparation method according to any one of claims 1 to 7, wherein the inner surface layer of the hollow fiber membrane is immobilized with a cationic copolymer.
9. The hollow fiber membrane according to claim 8, characterized in that The thickness of the inner surface layer of the hollow fiber membrane is 5 μm to 15 μm, and the thickness of the outer surface layer of the hollow fiber membrane is 25 μm to 35 μm.
10. A hollow fiber membrane obtained by the preparation method according to any one of claims 1 to 8, or use of the hollow fiber membrane according to claim 8 or 9 in hemodialysis.